PROBLEM OF CONTACT FOR A SYSTEM OF THE TYPE MINDLIN-TIMOSHENKO WITH INTERNAL DISSIPATION - Pérez Salvatierra, Alfonso (2013)
In this work we consider the one-dimensional dynamic model Mindlin- Timoshenko Beam. We will study the existence of soluciones for a contact problem associated with the Mindlin-Timoshenko system. Also analyze how energy decays exponentially to zero as time goes to infinity. The proposed system is as follows…